IMPLEMENTASI AKAD MUDHARABAH PADA PRODUK SIMPANAN IDUL FITRI (SI-FITRI) - M. Mun'im (Program Studi Ekonomi Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Al Hikmah Indonesia, 2025)
This study discusses the implementation of the mudharabah contract in the Eid al-Fitr Savings (Si-Fitri) product at KSPPS BMT NU Singgahan Bangilan Branch, which aims to analyze how the mudharabah contract is applied in the product to help the community prepare for their needs ahead of Eid al-Fitr. The research method used is qualitative descriptive with a case study approach, where data is collected through interviews, observations, and document analysis. The results of the study show that the mudharabah contract is applied with sharia principles, where the customer as the owner of capital submits funds to BMT to be managed in halal and productive micro businesses, with a profit share of 17% of the surplus of business results (SHU). In addition, customers also get Hari Raya gifts as an additional benefit. The implementation of the mudharabah contract in this product provides double benefits, namely for BMT in increasing profitability and for customers in planning better finances in accordance with Islamic law. This product also plays a role in supporting the development of the micro-economy in the Bangilan area and its surroundings.